Indoor Thermal Assessment of Post Tsunami-Housing in Banda Aceh, Indonesia - Laina Hilma Sari (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
The purpose of the study is to see and evaluate the annual indoor thermalperformance of post tsunami housing in Banda Aceh, Indonesia by comparing the data with the annual inside thermal performance of unaffected existing house and Acehnese traditional house and the neutral temperatures in tropics. This study is approached by analysing the results of a field survey carried out using questionnaires, onsite measurements, and the relevant literatures. The further analysis in predicting the annual indoor thermal performance was conducted using TAS thermal analysis simulation software. The finding show that there is no significant difference in inside air temperature between thepost-tsunami housing and the unaffected existing housing (except traditional Acehnese houses). This study performs the actual indoor thermal performance in the post tsunami housing for couple of days and the predicted annual data of the houses simulated using TAS software. This information is valuable for both the government and Non-Governmental Organizations who carried out the post reconstruction programs in performing their „products‟ (donated houses) dealing with the long term local climate